Fabrication and characterisation of a fully auxetic 3D lattice structure via selective electron beam melting - Warmuth, Franziska; Osmanlic, Fuad; Adler, Lucas; Lodes, Matthias A; Körner, Carolin (Smart materials and structures, 2017)
A three-dimensional fully auxetic cellular structure with negative Poisson's ratio is presented. Samples are fabricated from Ti6Al4V powder via selective electron beam melting. The influence of the strut thickness and the amplitude of the strut on the mechanical properties and the deformation behaviour of cellular structures is studied.